Systematic Review: Measurement Methods and Concept of Resilience Among Seafarers - Wiebke Janssen; Hans-Joachim Jensen PhD; Volker Harth MD; Marcus Oldenburg MD (SAGE Publishing, 2024)
Shipping is considered a demanding environment that can significantly impact seafarers' well-being and mental health. This review aims to examine existing literature on the resilience of seafarers, with a focus on the measurement methods used. Furthermore, this study intends to gain a comprehensive understanding of the current state of research in the field of seafarers' resilience, examining the variations in defining and conceptualizing resilience across different studies and contexts. The review identified 99 studies published between 2003 and 2023, with ten studies being included in the final analysis. These studies employed various measurement methods and provided definitions of resilience. Five questionnaires were identified, with the Dispositional Resilience Scale-15 (DRS-15) being the most commonly used. Two of the selected studies had a longitudinal follow-up, while eight were cross-sectional. Four studies related to tankers, and an additional four studies focused on naval vessels, while two studies did not specify the vessel type. The publications were distributed in the period between 2003 and 2013 (two papers) and between 2013 and 2023 (eight papers). The identified themes encompassed shipboard stressors (three papers), sleep problems (two papers), occupational groups or attitudes (two papers), experiences in war (two papers), and intervention measures (one paper), highlighting the multidimensional nature of resilience within the maritime field. This review suggests a research gap, as it reveals that the topic of resilience in seafaring has been sparsely represented. Despite an increasing interest in recent years, research remains limited, particularly in the civilian maritime sector. Therefore, this review highlights the importance of understanding and promoting resilience among seafarers. While the variety of questionnaires used was limited, achieving consensus and standardization in resilience measurement is essential for more comparable and consistent research findings. Recognizing resilience as a crucial resource can promote the development of targeted interventions and support systems, enhancing seafarers' well-being and mental health.